Pueraria mirifica, phytoestrogen-induced change in synaptophysin expression via estrogen receptor in rat hippocampal neuron - Rattiya Chindewa (2018)
Objective: To examine Pueraria mirifica (Leguminosae) containing- phytoestrogen effect on synaptic density and involvement of estrogen receptor. Material and Method: The level of synaptophysin, a presynaptic vesicle protein, was measured using Western blot analysis and immunocytochemistry in hippocampal primary cell cultures at 6 days in vitro. Results: P. mirifica and 17?-estradiol (0.1 ?M) treatment for 4 days, but not for 2 days, significantly increased synaptophysin immunoreactivity and level of synaptophysin. P. mirifica up to 60 ?g/ml resulted in a dose related increase in the level of synaptophysin immunoreactivity. The classical estrogen receptor antagonist, ICI 182 780, significantly blocked P. mirifica-induced increase in synaptophysin. Conclusion: P. mirifica-containing phytoestrogen affects synaptic density by inducing synaptophysin expression via estrogen receptor.